Studi Literatur: Pengembangan Talenta Digital untuk Transformasi Digital di Sektor Jasa Keuangan - Afrizal; Gultom, Pesta; Januarty, Widalicin; Claudie Tiofanny (LPPM STIE EKA PRASETYA, 2025)
Digital transformation has fundamentally changed the financial services sector, demanding the presence of skilled digital talent capable of adapting to and leveraging technologies such as Cybersecurity, Cloud Computing, Big Data Analytics, and Artificial Intelligence. This research aims to explore the role of higher education in developing the digital talent necessary to accelerate digital transformation in this sector. This study employs a qualitative-descriptive research design with a literature review approach. The literature review was conducted by collecting articles from reputable international journals indexed in Scopus that align with the research objectives over the past five years (2019-2024) using the Publish or Perish (PoP) application. Content analysis was then performed to identify the challenges and opportunities in creating a relevant curriculum for developing digital talent in the financial services sector in Indonesia through higher education, as well as how this can support the acceleration of digital transformation. The results indicate that collaboration between higher education and industry, along with government policy support, is crucial for creating a competitive and innovative financial ecosystem. This research recommends the development of educational programs that emphasize digital skills and adaptive capabilities to meet the ever-evolving market needs.